Dinamika Kewarisan di Kabupaten Bone: Menggali Faktor Pemicu Sengketa dan Upaya Rekonstruksi Pembagian Warisan - Andi Tenri Leleang; umar P (Fakultas Hukum Universitas Ichsan Gorontalo, 2026)
This study aims to understand the dynamics of inheritance in Bone Regency. The study focuses on identifying the triggering factors for inheritance disputes by examining the existence of customary law and the role of philosophical values ​​held by the Bugis Bone community, as well as the solutions offered in reviving Islamic values ​​and ensuring that the concepts prevailing in Bone Regency are in accordance with the provisions of religious teachings. The study was conducted using a field research model presented qualitatively and a normative-sociological approach. The results of the study obtained that inheritance disputes in Bone Regency were triggered by the fading values ​​of sipakatau, sipakalebbi, and sipakainge, as well as the wavering of a person's siri' value, which was exacerbated by legal pluralism that gave rise to contradictions between Islamic law and customary law to influence inheritance distribution practices in society; this condition also shows that non-litigation solutions contain hidden dangers, so that a solution in the form of legal reconstruction is needed to regenerate Islamic values ​​through collaboration and synergy of related stakeholders.